New thinking in Austrian political economy - Coyne, Christopher J.; Storr, Virgil Henry 1975- (Emerald, 2015)
The theme of this volume is 'New thinking in austrian political economy'. It includes original research by scholars working within Austrian political economy. The contributors draw on insights from Austrian economics shed new light on a range of relevant topics including: the role of culture in economic action, the political economy of postdisaster recovery, class structure, decentralized political orders, drones, institutional change, macroeconomics, and superstition and norms. Each chapter discusses the relevance of Austrian political economy for understanding the topic under analysis and discusses areas for future exploration and research. The volume captures the relevance of Austrian political economy for scholarship on a wide array of topics and its potential as an active and openended research program. Scholars working in the areas of Austrian economics, heterodox economics, constitutional political economy, cultural studies, political science, public choice, sociology, and public policy will find the volume of interest.